2014
DOI: 10.2174/1876396001407010033
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effect of Ferulic Acid on NF-kB, COX-2 and VEGF Expression Pattern During 7, 12-Dimethylbenz(a)anthracene Induced Oral Carcinogenesis

Abstract: Ferulic acid, a natural antioxidant, has the potential to prevent inflammation and to modulate angiogenesis in both in vivo and in vitro models. The present study has investigated the modulating effect of ferulic acid on the expression pattern of COX-2, NF-B and VEGF during 7,12-dimethylbenz(a)anthracene (DMBA) induced hamster buccal pouch carcinogenesis. Over expression of COX-2, NF-B and VEGF was noticed in the oral tumor tissues of hamsters treated with DMBA. Oral administration of ferulic acid at a dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Thus, on the one hand, the presence of ferulic acid present in the three extracts and, on the other hand, the exclusive presence of Naringenin and Apigenin in F0. Zheng et al (2019); Zhou et al (2020) and Manoharan et al (2014) agree in pointing out the modulating effect of NF-kB when administering ferulic acid in animal models. In all three studies, a significant decrease in IL-6, TNF-α and IL-1β was reported.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, on the one hand, the presence of ferulic acid present in the three extracts and, on the other hand, the exclusive presence of Naringenin and Apigenin in F0. Zheng et al (2019); Zhou et al (2020) and Manoharan et al (2014) agree in pointing out the modulating effect of NF-kB when administering ferulic acid in animal models. In all three studies, a significant decrease in IL-6, TNF-α and IL-1β was reported.…”
Section: Discussionmentioning
confidence: 75%